A GENETIC VARIANT OF ANGIOTENSIN RS699 ASSOCIATED WITH DIABETIC NEPHROPATHY IN PATIENTS OLDER THAN 50 YEARS OLD - Anggelia Puspasari; Elfiani Elfiani; Citra Maharani; Susan Tarawifa (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
ABSTRACT Background: Beyond controlling blood pressure and blood glucose, a genetic factor may play role in diabetic nephropathy (DN) progression in Type II Diabetes Mellitus (T2DM). Previous studies reported a genetic variant of Angiotensin rs699 (M235T) associated with diabetic nephropathy, with conflicting results across populations worldwide. To the best of our knowledge association of this genetic variant has never been conducted in the Jambi Malay population. Aims The Aims of this study is to the reveal association of the genetic variant of Angiotensin rs699 with diabetic nephropathy in the Jambi Malay population. Methods: This study design was cross-sectional. Totally 70 T2DM patients aged 22-67 years old were participated, as many 41 patients have aged older than 50 years old. Genotyping was performed using tetra ARMS PCR specific for rs699. Result: Patients aged older than 50 who have CTTT genotype have lower risk for suffering DN than CC genotype (p-value 0.029; OR (95% CI) 0.233 (0.06-0.88)), the statistic significant persist in multivariate analysis (p-value 0.030; OR (95% CI) 0.19 (0.04-0.86)). Conclusion: CTTT genotype was protective for DN in patients older than 50 years old. Further study with larger sample size, multi-centre and measuring confounding factors was needed. Keyword: Genetic variant of Angiotensin, rs699, diabetic nephropathy, Type II Diabetes Mellitus, Malay population ABSTRAK Latar belakang: Kendali Tekanan darah dan glukosa darah saja tidak cukup untuk mencegah kejadian nefropati diabetik (DN) pada Diabetes Mellitus Tipe II (T2DM), faktor genetik juga berperan penting. Studi sebelumnya melaporkan varian genetik Angiotensin rs699 (M235T) yang terkait dengan DN, dengan hasil yang berbeda antar populasi. Sejauh studi literatur yang dilakukan, varian genetik ini belum pernah diteliti pada populasi Melayu Jambi. Tujuan dari penelitian ini adalah untuk mengetahui hubungan varian genetik Angiotensin rs699 dengan nefropati diabetik pada populasi Melayu Jambi. Metode: penelitian ini merupakan penelitian potong lintang. Sebanyak 70 pasien T2DM berusia 22-67 tahun berpartisipasi, 41 diantaranya berusia lebih dari 50 tahun. Genotyping dilakukan dengan menggunakan tetra arms PCR spesifik untuk rs699. Hasil: Pasien berusia lebih dari 50 tahun yang memiliki genotipe CTTT memiliki risiko lebih rendah untuk menderita DN daripada genotipe CC (nilai p 0,029; OR (95% CI) 0,233 (0,06-0,88)), analisis multivariat juga menunjukkan hasil serupa (nilai p 0,030; ATAU (95% CI) 0,19 (0,04-0,86)). Kesimpulan: CTTT genotipe adalah pelindung untuk DN pada pasien yang lebih tua dari 50 tahun. Studi lebih lanjut dengan ukuran sampel yang lebih besar, berbagai pusat studi dan mengukur faktor risiko genetik dan non-genetik lain perlu dilakukan. Kata kunci: Varian genetik angiotensin, rs699, nefropati diabetik, Diabetes Mellitus Tipe II, populasi Melayu